Pendidikan Kesehatan Reproduksi terhadap Sikap Remaja tentang Seksual Pranikah - Nurafriani Nurafriani; Sarwin Mahmud; Anggeraeni Anggeraeni (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effect of reproductive health counseling on adolescent attitudes about premarital sex in high school students Cokroaminoto Tamalanrea Makassar. The research design was pre-experimental with one group pretest-posttest research design. The results of this study indicate that the category of premarital sexual attitudes is Good as many as 34 respondents or 69.4%, the results of bivariate analysis obtained the value of Sig. (2-tailed) 0.001 < = 0.05. In conclusion, there are differences in attitudes before and after being given reproductive health education. Keywords: Reproductive Health; Teenager; Premarital Sexual, Attitude